Case Report: Second-line favourable effect of pembrolizumab plus chemotherapy in a patient with metastatic hepatoid adenocarcinoma of the stomach - Tang, Yao; Li, Xiaofen; Yang, Yu (Frontiers in Pharmacology, 2025)
Hepatoid adenocarcinoma of the stomach (HAS) is a rare and aggressive malignancy with poor prognosis. HAS is characterized by both adenocarcinoma and hepatocellular carcinoma like differentiation, which often produces alpha-fetoprotein (AFP) and responds poorly to systemic chemotherapy. Herein we report a case of 62-year-old male diagnosed with liver metastatic HAS, who progressed rapidly after first-line cisplatin + fluorouracil chemotherapy combined with pembrolizumab. However, the patient achieved favourable outcome after second-line oxaliplatin + capecitatine chemotherapy combined with pembrolizumab. This case indicated that the chemotherapy regimen might influence the efficacy of immune check-point inhibiors plus chemotherapy.